Mixed ciliary-capsular fixation of a three-piece IOL during phacoemulsification in patients with the lenticular ligamentous-capsular system’s failure - B.E. Malyugin; E.N. Panteleev; L.L. Khapaeva; A.G. Savenkov (Офтальмохирургия)
Purpose. To evaluate clinical results of mixed ciliary-capsular fixation of a three-piece IOL in combination with the intracapsular ring’s implantation during phacoemulsification in patients’ zonular weakness caused by pseudoexfoliative (PEX) syndrome. Material and methods. This study included 78 patients (86 eyes) with complicated cataract and PEX syndrome associated with zonular weakness and natural lens instability. The average age of the patients was 74.3±9.3 years. Phacoemulsification was performed in a standard technique and followed by ciliary-capsular fixation of a three-piece IOL in all cases. Preoperative and postoperative follow up period lasted from 1st day until 10 months postop. It included biomicroscopy, visual acuity measurement, keratometry, tonometry, ultrasonic biomicroscopy, optical coherence tomography of the posterior segment of the eye. Results. At the 2nd day postop (86 cases) UCVA and BCVA were 0.46±0.29 and 0.58±0.27 respectively, IOP was 16.48±2.81 mm Hg; at 10 months postop (38 cases) UCVA and BCVA – 0.54±0.31 and 0.79±0.28, IOP – 15.34±3.71 mm Hg. The average deviation of the predicted refraction at the 2 days after surgery was –0.29±0.77 D with no significant change after 10 months. Efficiency ratio at 10 months postop was 193, the safety factor was 285. This type of IOL fixation didn’t lead to an increase in IOP, development of chronic inflammation such as iridocyclitis or any other comorbidity. All IOLs were stable position regardless of the status of the zonular fibers. Conclusion. As a result of a preliminary study, it was found that mixed ciliary-capsular fixation of a three-piece IOL provides its stable position, high clinical and functional results in the early and late postoperative period after phacoemulsification in patients with pseudoexfoliative syndrome and failure of the lenticular ligamentous-capsular system.